Anatomical Studies on the Reticular Groove of Adult Non-descript Sheep of Jammu Region - Sasan, Jasvinder Singh; Suri, Shalini; Sarma, Kamal (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted at the Division of Veterinary Anatomy from 2021–2022 to understand the functional aspect of reticular groove and scarcity of literature in sheep. Reticular groove was characterized by floor and two muscular lips extending from the cardia to the level of reticulo-omasal opening. Both the lips were prominent and more developed in the aboral part than in the oral part. The left lip was cranial whereas the right lip was more caudal in position. The width was maximum in middle. Papillae resembling the claws of a small bird.were seen towards reticulo-omasal opening. Histologically, reticular groove was lined by stratified squamous keratinized epithelium. Incomplete lamina muscularis mucosae was seen mainly in the lips. Lamina propria blended with tunica submucosa. In the floor of groove, mainly transverse smooth muscle fibers were seen whereas lips contained thick longitudinal smooth muscle fibers. The epithelium and keratin layer were thicker at lips. Lamina propria submucosa was thicker at floor. Histochemically, strong positive PAS reaction was seen in the stratum corneum whereas basement membrane showed moderate PAS reaction. Cells of stratum granulosum showed strong reaction for Alcian Blue (pH 2.5) whereas other layers showed moderate reaction for Acid mucopolysaccharides with Alcian Blue (pH 2.5). Glycogen was moderately observed in the lamina epithelialis except stratum corneum. Layers of lamina epithelialis and tunica muscularis showed strong reaction for basic proteins. Stratum corneum showed strong reaction for lipids whereas other layers were weak to moderately positive.